2021
DOI: 10.3389/fpsyg.2021.727250
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Anxiety and Postoperative Pain in Patients With Laparoscopic Hysterectomy

Abstract: Objective: This study was designed to investigate preoperative anxiety situations and postoperative pain degree in Chinese patients undergoing laparoscopic hysterectomy and to analyze the related factors of preoperative anxiety and the correlation between preoperative anxiety and postoperative pain to provide a reference for effective postoperative analgesia management.Methods: A total of 100 female patients undergoing laparoscopic hysterectomy were enrolled in this study and randomly divided into two groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…It suggests that preoperative psychological status is as significant as the physiological status and surgical effect in assessing the occurrence of postoperative pain. 16 As revealed in our study, preoperative anxiety and depression are risk factors for acute pain after laparoscopic radical resection of colorectal cancer in elderly patients. Furthermore, prior research has demonstrated that patients with high levels of preoperative anxiety tend to have more intense postoperative pain despite receiving adequate intraoperative pain relief.…”
Section: Discussionmentioning
confidence: 58%
“…It suggests that preoperative psychological status is as significant as the physiological status and surgical effect in assessing the occurrence of postoperative pain. 16 As revealed in our study, preoperative anxiety and depression are risk factors for acute pain after laparoscopic radical resection of colorectal cancer in elderly patients. Furthermore, prior research has demonstrated that patients with high levels of preoperative anxiety tend to have more intense postoperative pain despite receiving adequate intraoperative pain relief.…”
Section: Discussionmentioning
confidence: 58%
“…Some studies showed that gynecological elective surgical patients with a high anxiety trait need an increased dose of propofol for the induction and maintenance of anesthesia, while anxious patients undergoing cholecystectomy have a higher risk of intraoperative hemodynamic events (15,16). Moreover, as previously reported, the correlation between preoperative anxiety and the reduction of pain threshold leads to an increased requirement for analgesic drugs (14, [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 83%
“…It is well-documented that increased anxiety prior to endoscopic procedures is associated with increased physiologic stress, worse outcomes (pain, mood deterioration, and mortality), and decreased patient satisfaction. 23 24 Improving the overall patient satisfaction promotes patient-physician relationships, as well as patient recovery and compliance. Sedative premedication, first used to reduce anxiety prior to endoscopic procedures, has recently been shown to result in no remarkable improvement in the overall satisfaction of patients.…”
Section: Discussionmentioning
confidence: 99%